Studi Literatur: Pengembangan Instrumen Tes Berbasis Literasi Kimia di Indonesia - Imaltin, Suciana (Lembaga Yasin AlSys, 2024)
The chemical literacy skills of students in Indonesia are currently low. Chemical literacy is very important to be applied in students because the development of the 21st century requires quality, reliable, and globally competitive human resources (HR). The purpose of this study is to review the development of chemical literacy test instruments from 2019-2023. Article collection was carried out using Google Scholar and Publish and Perish software with the keywords assessment test, instrument test, chemical literacy. The review results show that in general, chemical literacy test instruments can improve students' chemical literacy. However, the material developed is still very minimal so it is necessary to develop other chemical materials. Then it can be seen that the development of chemical literacy test instruments in Indonesia is still small. This can be seen in 2023 only one development of chemical literacy instruments. It is hoped that the next researcher can pay attention to the material, the level of education in accordance with the latest curriculum.